Pelatihan Peer Counseling Bagi Siswa SMA Ya Bakii Kesugihan - Endang Rifani; Syifaul Ummah; Nikmah Maulina; Dewi Lestari; Ulfatul Musrifah (Yayasan Daarul Huda Kruengmane, 2023)
School is a place for students to optimize their personal and academic development. In the process, students have a need to interact with their peers, the results of a survey of high school students Ya BAKII 01 Kesugihan show that students are more happy when telling stories with their peers compared to gudance and counseling teachers as a means to reduce the tension they experience, especially related to personal, social, and social problems. and study. The solution to this problem is to prepare an extension through training for selected students so that they can help students who need assistance, this is called peer counseling. Students who are trained go through a selection stage with criteria; 1) have good academic achievement; 2) have good behavior; 3) have high empathy; 4) able to cooperate with other people; 5) open to others; and 6) be responsible. Selection based on these criteria is carried out in accordance with the qualifications and standards of the peer counselor. The purpose of peer counseling training is to provide knowledge and competency-based skills as peer counselors. The method of implementing this community service activity uses a form of training which is carried out through several stages, namely socializing the activity program, carrying out training which includes theory, simulation, and evaluation during two meeting sessions. The results of the training are contained in this article.